The conception of decent care the cardiac person from the perspective of nurses: integrative review (Research, Society and Development, 2022)
Objective: to know the conceptions of dignified care of the cardiopathic person from the perspective of nurses. Study conducted between October and November 2019 in the following LILACS, MEDLINE and PUBMED databases. Articles published in full between 2015 and 2019 were included. The degree of adequacy of each article was performed using a Likert scale. Of the 11 articles selected, 8 articles obtained 4 points, that is, relevant to the methodology, results, conclusion. Results: In the nurses' conception there are limitations for decent care such as distrust, communication, judgment, lack of privacy, physical restriction, neglected hygiene, stress, routines, decision making, intense workload and scarcity of employees. It is necessary to reflect and discuss individually and with their peers about how dignity can be applied, considering the needs of individuals and opportunistic knowledge and experience of health professionals.